Implementasi Pengenalan Fiqih Dasar pada Anak Usia Dini dalam Membangun Karakter Islami di SB At-Tanzil Serdang - Khoiroh, Sabilatul; Rahman, Taufiqur; Hisyam, Mohamad Ali (Keris: Journal of Community Engagement, 2025)
This service aims to explore education and the deepening of basic fiqh for immigrant children who are students at the At-Tanzil Serdang Guidance Center in Malaysia. The difficulty of accessing education poses a challenge for immigrant children, especially in understanding religious studies due to cultural differences between Indonesia and Malaysia. This community service uses a base community research approach, which is implemented through education at Sanggar Bimbingan At-Tanzil Serdang, Malaysia, such as providing learning through theory, books, short quizzes, and educational videos via the YouTube application related to basic fiqh. The results of this community service show a significant improvement in performing prayers correctly and properly according to the teachings of the KKN students. This program has proven effective in enhancing students' ability to learn basic fiqh to form an Islamic character in a short period. Students show significant enthusiasm towards the educational process and demonstrate competent abilities to effectively apply basic fiqh principles in their daily activities.